2011
DOI: 10.1038/ja.2011.89
|View full text |Cite
|
Sign up to set email alerts
|

Establishment of norvancomycin fluorescence polarization immunoassay for therapeutic drug monitoring

Abstract: To establish a rapid and simple fluorescence polarization immunoassay method for determination of norvancomycin serum concentration, we collected 300 serum samples from the patients receiving norvancomycin in the hospitals localized in Shanghai, China. The drug concentrations were measured by the established HPLC method and FPIA with vancomycin kit. A FPIA algorithm for the determination of norvancomycin concentration was established according to the correlation between the FPIA and HPLC results. The methods a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 17 publications
0
3
0
1
Order By: Relevance
“…The volume of ultrafiltration solution could be controlled by the inner diameter of the hollow fiber tube, avoiding the influence of the ultrafiltration solution volume on the accuracy of analysis. Compared with the protein precipitation method (Lima et al, 2018; Wu et al, 2012), the sensitivity of this method was 2–4 times higher, and the accuracy could reach 95.1%, surpassing 82.6% of CF–UF (Parker et al, 2017). The centrifugation time in this study was 5 min, shorter than the 20 min reported in the literature (Kees et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…The volume of ultrafiltration solution could be controlled by the inner diameter of the hollow fiber tube, avoiding the influence of the ultrafiltration solution volume on the accuracy of analysis. Compared with the protein precipitation method (Lima et al, 2018; Wu et al, 2012), the sensitivity of this method was 2–4 times higher, and the accuracy could reach 95.1%, surpassing 82.6% of CF–UF (Parker et al, 2017). The centrifugation time in this study was 5 min, shorter than the 20 min reported in the literature (Kees et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…ИФА нашел свое развитие в виде флуоресцентного поляризационного иммуноанализа [41], который основан на возрастании поляризации флуоресценции небольших флуоресцеин-меченных молекул антигена (трейсеров) при их взаимодействии со специфическими антителами. Если в тестируемом образце содержится лекарственное вещество, то трейсер будет конкурировать с ним за связывание с антителами, и значение поляризации флуоресценции будет Наиболее современным хроматографическим методом аналитического определения лекарственных веществ является жидкостная хромато-масс-спектрометрия, особенно в тандемном варианте (ЖХ-МС-МС) [42].…”
Section: мониторингunclassified
“…Norvancomycin shows pharmacological properties and antibacterial activities similar to those of vancomycin, which exhibits significant inhibitory activity against Gram-positive cocci and bacilli , especially to methicillin-resistant Staphylococcus aureus (MRSA) and methicillin-resistant Staphylococcus epidermidis (MRSE). Due to its potential clinical application, norvancomycin was commercially developed by the North China Pharmaceutical Company and has been widely used in China to treat endocarditis, osteomyelitis, and other severe infections caused by S. aureus (including methicillin-resistant strains) ( 2 ) for >3 decades. Genome sequencing of A. orientalis CPCC200066 may provide information for discovering the biosynthetic gene cluster for norvancomycin.…”
Section: Genome Announcementmentioning
confidence: 99%